2019
DOI: 10.1111/sms.13415
|View full text |Cite
|
Sign up to set email alerts
|

Trunk exercise training improves muscle size, strength, and function in older adults: A randomized controlled trial

Abstract: The aim of this study was to assess the effectiveness of a multimodal exercise program to increase trunk muscle morphology and strength in older individuals, and their associated changes in functional ability. Using a single‐blinded parallel‐group randomized controlled trial design, 64 older adults (≥60 years) were randomly allocated to a 12‐week exercise program comprising walking and balance exercises with or without trunk strengthening/motor control exercises; followed by a 6‐week walking‐only program (detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 46 publications
2
31
1
Order By: Relevance
“…Older subjects rely more strongly on excessive activity of their back muscles to regulate energy transfer during gait [9]. Previous studies have reported that back extensor muscle strength affects dynamic balance and postural control in older adults [19,20]. Greater ES muscle activity in this study may imply that back muscle activity is increased during the whole gait cycle in older people so as to stabilize the trunk and to maintain a dynamic balance in accordance with increased treadmill inclination.…”
Section: Discussionmentioning
confidence: 62%
“…Older subjects rely more strongly on excessive activity of their back muscles to regulate energy transfer during gait [9]. Previous studies have reported that back extensor muscle strength affects dynamic balance and postural control in older adults [19,20]. Greater ES muscle activity in this study may imply that back muscle activity is increased during the whole gait cycle in older people so as to stabilize the trunk and to maintain a dynamic balance in accordance with increased treadmill inclination.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, we noted that the level of tness of our patients was relatively low. For example, patients studied by us performed on average 12 repetitions in chair stand tests, whereas 64 older adults (≥ 60 years) studied by Shahtahmassebi et al [41] performed approximately 16 repetitions before undertaking exercise, and even 20 repetitions after 18 weeks of training. Roongbenjawan and Siriphorn [42] indicated that a low number of repetitions in this test may signi cantly increase the risk of falls, because people who reported falls were able to perform only approximately nine repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction and magnitude of postural sway associated with the presence or severity of HV remain inconclusive. Furthermore, previous studies have suggested that muscle mass is a potential confounder of the HV status and postural sway [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%